A CONCEPTUAL MODEL FOR BALANCE BENWEEN SECURITY AND USABILITY IN SOFTMARE - Крихівський, Михайло (SWorldJournal, 2025)
The article presents the concept of a Dynamic Multi-Level Authentication Model (DMAA), which offers an innovative approach to ensuring user security in a digital environment. The author explores the challenges of traditional authentication methods, which